تصميم وقياس هوائي مصفوف لوغاريتمي دوري LPDA عريض الحزمة - عزيز يوسف (Tishreen University, 2018)
The wireless communication devices became very important. they have been developed fastly in the last few years. so, it must develop in many sides like electronic circuits, applications, electrical wires, transmit and receive antennas and others. Our search is about design and measure a kind of wide band antennas, in some applications that work on frequency range, the antenna is designed on medial frequency and its response changes noticeably according to changes of frequency, and it may be disappeared on some frequencies, in the wide band antennas this problem had solved, because its response stay suitable among the frequency range of antenna, and it leads to got gain, responded, and good radiation pattern. In this research we designed LPDA antenna using visual basic application, And tested it in microwave and antenna laboratory and compared with Yagi uda antenna. أصبح لوسائل الاتصالات اللاسلكية دوراً مهماً لا غنى عنه في حياتنا العملية وتطورت على مر الزمن بشكل سريع وفي شتى المجالات خصوصاً في العقود القليلة الماضية, وتطلب ذلك مواكبة هذا التطور على كافة الأصعدة من دارات الكترونية وبرامج حاسوبية وكابلات ناقلة وأيضاً هوائيات ارسال واستقبال وغير ذلك الكثير. نهتم في بحثنا هذا بتصميم وقياس نوع من الهوائيات عريضة الحزمة حيث أنه وفي بعض التطبيقات التي تعمل على مجموعة من الترددات. يصمم الهوائي على تردد وسطي وتتغير استجابته بشكل ملحوظ مع تغير التردد وقد تنعدم عند ترددات مغايرة للتردد الأساسي, أما في الهوائي عريض البند فيتم تجاوز هذه المشكلة حيث ان استجابته تحافظ على مستوى جيد دون انعدام ضمن المجال الترددي المصمم لأجله الهوائي مما يفيد بالحصول على ربح ومردود وعرض حزمة اشعاعية جيدة. تم في هذا البحث تصميم هوائي (LPDA) باستخدام تطبيق صممناه على برنامج visual basic واختبر في مخبر الهوائيات والأمواج المكروية وتمت مقارنته مع هوائي ياغي يودا.